Dobro dziecka a stosowanie procedur wspomaganej medycznie prokreacji w prawie francuskim i prawie polskim: [The child’s interest in medically assisted procreation according to French and Polish law] (Studia Prawnicze / The Legal Studies, 2011)
Od kilku lat w Polsce trwa ożywiona dyskusja bioetyczna na temat konieczności uregulowania problematyki dokonywania zabiegów wspomaganej medycznie prokreacji. W chwili obecnej w Sejmie znajdują się cztery projekty ustaw odnoszące się do tej materii. Przedmiotem analizy w prezentowanym artykule będą rozwiązania francuskie w zakresie ochrony dobra dziecka w procedurach wspomaganej medycznie prokreacji oraz propozycje w zakresie uregulowania omawianej materii w prawie polskim w kontekście rozwiązań przyjętych w prawie francuskim The purpose of this article is to present analysis of the term „child’s interest” in some aspects of medically assisted procreation. The object of analysis is on the one hand French legal regulation of medically assisted procreation techniques and, on the other hand, the state of Polish preparations to conclude the legal process of bioethical law. As there is no legal definition of „child’s interest”, the authors present state of French and Polish doctrine in this subject. The article answers the question whether and how it is possible to refer to the term „child’s interest” in the situation of an unborn child and even more a child who only is to be concepted. Authors especially concentrate their attention on the requirements allowing to apply medically assisted procreation. Child’s interest is taken into consideration during the process of creation and application of „medically assisted procreation methods” law. Therefore, the medically assisted procreation techniques should be applied only in case of sterility or infertility and couples should fulfill some personal conditions (i.e. to be married or, according to French regulation, in a stable relationship, to be alive and in the age in which people usually procreate).